Tumor necrosis factor-alpha inhibits albumin gene expression in a murine model of cachexia. - Brenner, D A (1990)
The mechanisms responsible for decreased serum albumin levels in patients with cachexia-associated infection, inflammation, and cancer are unknown. Since tumor necrosis factor-alpha (TNF alpha) is elevated in cachexia-associated diseases, and chronic administration of TNF alpha induces cachexia in animal models, we assessed the regulation of albumin gene expression by TNF alpha in vivo. In this animal model of cachexia, Chinese hamster ovary cells transfected with the functional gene for human TNF alpha were inoculated into nude mice (TNF alpha mice). TNF alpha mice became cachectic and manifested decreased serum albumin levels, albumin synthesis, and albumin mRNA levels. However, even before the TNF alpha mice lost weight, their albumin mRNA steady-state levels were decreased approximately 90%, and in situ hybridization revealed a low level of albumin gene expression throughout the hepatic lobule. The mRNA levels of several other genes were unchanged. Hepatic nuclei from TNF alpha mice before the onset of weight loss were markedly less active in transcribing the albumin gene than hepatic nuclei from control mice. Therefore, TNF alpha selectively inhibits the genetic expression of albumin in this model before weight loss.